Memanfaatkan Platform Digital: Pendampingan Strategi Pemasaran Live Streaming TikTok untuk Meningkatkan Penjualan UMKM Chocolazo Indonesia Kota Kediri - Khoiriyah, Ikfi Fikla; Aini, Indah Noer; Triyani, Indri Dinda; Kumalasari, Indyka Ferninda; Ningtyas, Intan Dwi Kartika (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This assistance aims to increase sales for Indonesian Chocolazo MSMEs in Kediri City through the use of digital platforms, especially TikTok live streaming. The mentoring method is carried out by providing guidance and effective marketing strategies for using TikTok live streaming to achieve higher sales targets. The accompanying team will work closely with MSME owners to develop interesting content, appropriate promotional strategies, and effective communication skills to attract the attention of potential consumers. The results are expected to increase product visibility, increase interaction with customers, and ultimately increase sales of Chocolazo products. With this approach, it is hoped that Chocolazo Indonesia MSMEs in Kediri City can make maximum use of the potential of digital platforms to achieve success in marketing and selling their products.